In Silico Sequence Analysis Homology Modelling and Functional Annotation of Toxin I Hypothetical Protein of Catfish Plotosus lineatus - Thangaraj, Muthusamy (International Journal of Pharmaceutical & Biological Archive, 2014)
In Silico Sequence Analysis Homology Modelling and Functional Annotation of Toxin I Hypothetical Protein of Catfish Plotosus lineatus